A massif‐type (~1.86 Ga) anorthosite complex in the Yeongnam Massif, Korea: late‐orogenic emplacement associated with the mantle delamination in the North China Craton. (16th July 2014) - Lee, Yuyoung; Cho, Moonsup; Cheong, Wonseok; Yi, Keewook
Abstract To unravel the petrogenesis of a massif‐type anorthosite in terms of the crust‐mantle geodynamics, we dated zircons separated from six samples from the Sancheong‐Hadong (SH) complex, Korea, using a sensitive high‐resolution ion microprobe. The weighted mean 207Pb/206Pb age of two anorthosites is 1862 ± 2 Ma, whereas the ages of the hornblende gabbro and granitic gneiss are 1873 ± 4 Ma and 1875 ± 5 Ma respectively. Zircon rims from mafic granulite and migmatitic gneiss yielded ages of 1860 ± 5 Ma and 1858 ± 4 Ma, respectively, implying that the granulite facies metamorphism and anatexis are associated with anorthosite emplacement. Our results, together with available Re–Os data, are compatible with the ~1.9–1.86 Ga collisional orogeny prevalent in the North China Craton and the Korean Peninsula, and suggest that orogenesis was accompanied by mantle delamination beneath the craton. It is thus likely that the SH anorthositic rocks are a product of late‐orogenic magmatism during the post‐collisional extension‐dominated phase of orogeny.